Current practice of online business in Malaysia: the Sha’riah compliance - Abdullah @ Abd Aziz, Azilawati; Hussin, Siti Nor Adawiah; Awang @ Ab Rahman, Nurul Hidayah; Zainan, Nurul Izzah Noor (Universiti Teknologi MARA, Kelantan, 2018)
Globalization or international expansion has fundamentally and phenomenally changed the world economic landscape. The implication of globalization includes the expansion of the number of nation producing goods and distribution strategies, rapid technological evolution, lowered cost of communication and transportation and many more. Accordingly, due to the rise of global competition, all the business organizations nowadays are using internet as a medium of selling their products and services. Online business becomes common of people’s daily lives as such, people can purchase and sell various products and service through internet. Nowadays, the modern society in the developing countries have changed their practice in trading from conventional practices into the modern and cutting edge technology. The fast growth in the current business organizations are involving the “Online Business” between seller and buyers. This article is written down to examine and evaluate whether their current practice of online business is permissible in Islamic perspective or Islamic law. Online Business in Islamic perspective is defined as “to sale the product which has to include the product specification in the contract and pronounced with Salam or Salaf.”Therefore, the objectives of this paper are to identify whether the current practice of online business in Malaysia is in accordance with Islamic law of fiqh muamalat. This paper will look into both perspectives; online seller and online customer. This research paper concludes the current practice of online business which is in line with Islamic law of fiqh muamalat.